2019
DOI: 10.5032/jae.2019.03191
|View full text |Cite
|
Sign up to set email alerts
|

The Forms of Dissonance Experienced by U.S. University Agriculture Students During a Study Abroad in Nicaragua

Abstract: In spring 2018, nine agriculture students from Louisiana State University traveled to Nicaragua for a study abroad course. During this experience, students explored agricultural industries and engaged in cultural tours as well as in a service-learning project. Evidence has demonstrated that such experiences can transform students' intercultural sensitivity, global knowledge, and views on agriculture. To facilitate such an experience, however, requires educators to design experiences that challenge students' ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Students also articulated they experienced intellectual dissonance, or discrepancies regarding their existing knowledge, as they encountered new concepts, practices, and innovations in Costa Rica and Thailand that seemed to stand in contrast to their previous knowledge of U.S. agriculture. This finding supports those reported by O'Malley et al (2019). However, the final form of dissonance, moral, does not appear to have been explored previously.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Students also articulated they experienced intellectual dissonance, or discrepancies regarding their existing knowledge, as they encountered new concepts, practices, and innovations in Costa Rica and Thailand that seemed to stand in contrast to their previous knowledge of U.S. agriculture. This finding supports those reported by O'Malley et al (2019). However, the final form of dissonance, moral, does not appear to have been explored previously.…”
Section: Discussionsupporting
confidence: 88%
“…Mezirow (1991) explained that when individuals reflect on dissonance, it could spur a powerful learning process, called transformational learning (TL), by which individuals' previously held worldviews are transformed. O'Malley, Roberts, Stair, and Blackburn (2019) reported that university students experienced four forms of dissonance during a study abroad course to Nicaragua: (1) environmental, (2) sociocultural, (3) personal, and (4) intellectual. And, as a consequence of such dissonance, they experienced a transformation of their perspectives (O'Malley et al, 2019).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature on the role social influences play in serving as a primary motivation for agriculture students, especially regarding racial minority groups, to study abroad is scant. Finally, the Learning-Oriented Students, who were primarily female, reported their desire to gain more agricultural knowledge, experience an alternative method of instruction, and learn to work with diverse populations provided intrinsic value (Eccles et al, 1983) to encourage them to enroll in a study abroad course in the future, which is supported by literature reported in agricultural education (Danjean, et al, 2015;O'Malley et al, 2019;Raczkoski et al, 2018). Our findings, therefore, provided important insights into expectancy-value theory and practice regarding the design and delivery of study abroad courses.…”
Section: Discussionmentioning
confidence: 87%
“…The literature in agriculture has also explored the short-term impacts and best practices of study abroad courses (Bunch et al, 2018;Conner et al, 2019;Conner & Roberts, 2015;Dobbins et al, 2019Dobbins et al, , 2020O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a, 2020b. During short-term study abroad courses, existing evidence has demonstrated that students can began to reexamine their lifestyle, beliefs, attitudes, and behaviors (Dobbins et al, 2019(Dobbins et al, , 2020O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a. Despite this progress, the value and validity of short-term study abroad courses have consistently been called into question (Tarrant & Lyons, 2012).…”
Section: Introductionmentioning
confidence: 99%